Multicenter case series of standalone XEN implant vs. combination with phacoemulsification in Turkish patients - ERASLAN, MUHSİN; DERİCİOĞLU, VOLKAN (SPRINGER, 2021)
Purpose To evaluate and compare the efficacy, safety and needling timing and rates of standalone XEN implant vs. combination with phacoemulsification in Turkish patients. Methods Retrospective, multicenter study which included the data of patients, who had open angle glaucoma including primary open angle glaucoma and pseudoexfoliation glaucoma, underwent standalone XEN implantation (XEN alone) and combined surgery with phacoemulsification (XEN + Phaco) between 2016 and 2018. Results The study included 26 eyes of 24 patients in XEN alone group and 32 eyes of 30 patients in XEN + Phaco group. The mean intraocular pressure (IOP) was 23.3 +/- 6.0 mmHg and 24.4 +/- 7.4 mmHg at baseline (p = 0.838), and it reduced to 16.3 +/- 3.0 mmHg and 16.4 +/- 2.3 mmHg at 12-month follow-up (p = 0.436) in XEN alone and XEN + Phaco groups, respectively (reduction: %30 and %33, P = 0.642). The mean number of medications reduced from 2.9 + 0.7 before surgery to 0.9 + 0.9 on month 12. In XEN alone and XEN + Phaco groups, the needling rates were 42.3% and 31.2% (p = 0.491), and the mean time to needling was 3.7 +/- 3.2 months and 4.9 +/- 8.0 months (p = 0.696), respectively. Hypotonia (17.2%) and hyphema (10.3%) were the most frequent complications, respectively. In XEN alone and XEN + Phaco groups, partial success was achieved in 73.1% and 71.9% of eyes when defined as IOP < 18 mmHg with any medication, respectively (p = 0.920). Conclusion The XEN implant provides significant reduction in IOP and number of medications, either standalone or combination with phacoemulsification. Both procedures need intensive postoperative care, requiring needling in approximately one-third of patients.
Keywords: XEN implant; Minimally invasive glaucoma surgery; Primary open angle glaucoma; Glaucoma surgery; Phacoemulsification; INTRAOCULAR-PRESSURE; CATARACT; EFFICACY; GLAUCOMA; SAFETY; REDUCTION; SURGERY